RESEARCH AND ANALYSIS OF THE VARIATION OF THERMOPHYSICAL CHARACTERISTICS OF SMOKED CRUSHED LAMB TRANSPOND FAT AND HEAT EXCHANGE PARAMETERS DURING THE PROCEDURE OF DEHYDRATION OF GRANULES WITH PROTECTIVE FILM - A. A. Elmurzaev; N. D. Aisungurov; I. Y. Aleksanian; A. H. Nugmanov; Y. A. Maksimenko (Современная наука и инновации, 2022)
In recent years, the interest of researchers in extruded products with a developed structure obtained on the basis of raw materials of animal origin has increased, primarily as a source of high-quality fats, as well as as the basis of therapeutic and preventive nutrition products of various technological forms. One of the promising directions in this area is to expand the range ofproducts with a developed structure by changing their taste and aroma with natural smoky smoking, which ensures an increase in their shelf life.